Watch wolf / 3. - Lasky, Kathryn (Lasky, Kathryn. Wolves of the Beyond., 2011)
Faolan, a wolf born with a twisted paw, returns to the pack that left him for dead to prove himself worthy, but just before he takes his place of honor, as one of the Wolves of the Watch, a wolf goes missing and Faolan discovers that she has been kidnapped by bears.